2021
DOI: 10.1097/pcc.0000000000002758
|View full text |Cite
|
Sign up to set email alerts
|

A Communication Guide for Pediatric Extracorporeal Membrane Oxygenation

Abstract: Decision-making surrounding extracorporeal membrane oxygenation initiation and decannulation has become a key challenge in critical care. Nuanced communication skills and transparent discussions about prognosis are imperative during this lifesaving, yet high-risk and burdensome intervention. Serious illness conversation guides are proving beneficial for patients, families and staff to communicate uncertainty and facilitate shared decision-making toward goal-concordant care. While the literature emphasizes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…While it seems logical that ‘the only way to truly know what matters most and how they prefer to make decisions is to ask the patients and families’, evidence is also emerging for personalised communication strategies to promote goal-concordant care in adult medicine 8–10. Serious illness communication guides and decisional aids also tend to subscribe to this approach, although there is a paucity of paediatric literature 11–13…”
Section: Precision Decisions: Personalised Communication With Tailore...mentioning
confidence: 99%
“…While it seems logical that ‘the only way to truly know what matters most and how they prefer to make decisions is to ask the patients and families’, evidence is also emerging for personalised communication strategies to promote goal-concordant care in adult medicine 8–10. Serious illness communication guides and decisional aids also tend to subscribe to this approach, although there is a paucity of paediatric literature 11–13…”
Section: Precision Decisions: Personalised Communication With Tailore...mentioning
confidence: 99%
“…Serious illness conversation guides are proving beneficial for communicating uncertainty and facilitating shared decision-making among patients, families, and the medical team [8]. Moynihan et al [9] proposed a structured conversation guide for critical time points during pediatric extracorporeal membrane oxygenation support, including iterative discussions toward decannulation even when the outcome is unclear.…”
Section: Clinician Perspectivementioning
confidence: 99%
“…We found that not to be the case and the lack of association indicates that, in this analysis, children with neurologic disorders or disability were not at significantly higher risk of unfavorable outcomes compared with children without disabilities prior to ECMO. However, the high morbidity and mortality in both cohorts highlight that the decision to initiate ECMO support requires an approach with high-quality communication based on an ethical framework that incorporates family values and shared decision making for all patients (38).…”
Section: At the Bedsidementioning
confidence: 99%